Schelling's game theory : how to make decisions - Dodge, Robert, 1945- (New York ; Oxford : Oxford University Press, 2012)
Nobel Prize winner Thomas Schelling taught a course in game theory and rational choice to advanced students and government officials for 45 years. In this book, Robert Dodge provides in language for a broad audience the concepts that Schelling taught.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Schelling, Thomas C., -- 1921-; Economists -- United States -- Biography; Political scientists -- United States -- Biography; Nobel Prize winners -- United States -- Biography; Game theory